Efficacy and safety of dapagliflozin in patients hospitalized with COVID-19 with and without type 2 diabetes: a prespecified analysis of the DARE-19 randomized trial - Mohammad Abdel Jawad; Remo H. M. Furtado; Russell Esterline; Jan Oscarsson; Samvel B. Gasparyan; Gary G. Koch; Felipe Martinez; Omar Mukhtar; Subodh Verma; Anna Maria Langkilde; Philip Ambery; Shachi Patel; et al. (Cardiovascular Diabetology)
Abstract Background Although several previous studies tested SGLT2 inhibitors in the setting of an acute, non-cardiovascular illness, detailed information on their efficacy and safety among participants with and without type 2 diabetes (T2D) from double-blind randomized trials is lacking. In this secondary prespecified analysis of the Dapagliflozin in Respiratory Failure in Patients with COVID-19 (DARE-19) trial, we sought to evaluate the safety and efficacy of initiating dapagliflozin during acute illness with COVID-19 in patients with and without T2D. Methods The DARE-19 trial randomized 1250 patients hospitalized with COVID-19 and cardiometabolic risk factors to dapagliflozin or placebo. T2D was present in 636/1250 (50.9%) of the cohort. Dual primary outcomes were evaluated: prevention (time to new or worsened organ dysfunction or death) and a hierarchical composite outcome of recovery (change in clinical status by day 30). Key biomarkers (serum bicarbonate, estimated glomerular filtration rate [eGFR], hematocrit, and glucose) and safety were assessed in participants with and without T2D during index hospitalization. Results Among patients with T2D, the prevention outcome occurred in 10.9% receiving dapagliflozin versus 13.9% receiving placebo (hazard ratio [HR] 0.76, 95% CI 0.49–1.18). In patients without diabetes, the event rate was 11.5% with dapagliflozin versus 13.3% with placebo (HR 0.86, 95% CI 0.55–1.35; interaction p = 0.668). For the primary recovery outcome, no significant differences were observed between dapagliflozin and placebo groups regardless of diabetes status (interaction p = 0.222). Close laboratory monitoring revealed similarities in serum bicarbonate, eGFR, or hematocrit for the dapagliflozin and placebo groups, irrespective of T2D status. Any serious adverse event was reported in 12·7% of patients in the dapagliflozin group, 14·3% in the placebo group among patients with T2D, and in 8·5% of patients in the dapagliflozin group, and 11·9% in the placebo group in patients without T2D. Diabetes ketoacidosis was reported in two patients with T2D in the dapagliflozin group. Conclusions Initiating dapagliflozin in patients hospitalized for acute COVID-19 was well tolerated and safe, irrespective of T2D status. Serum biomarker levels remained stable and comparable between treatment groups, indicating no increased risk of adverse metabolic or renal effects with dapagliflozin in this clinical scenario. Trial registration The trial was registered on ClinicalTrials.gov (NCT04350593).